2016
DOI: 10.1177/0145445516650964
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cost and Reward Procedures With Interdependent Group Contingencies

Abstract: Disruptive behavior is considered the most common concern among general education teachers. Due to the nature of disruptive behavior amongst multiple students in the classroom, it ha been suggested that the most reasonable way of handling disruptive classroom behavior is through group contingencies while utilizing token economies. The present study evaluated the effectiveness of token economies within a general education classroom. Two elementary school teachers and their students participated. Conditions incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…treatment (Lee et al, 2017;McGoey & DuPaul, 2000). The present study extends the research on the effectiveness of variations of the GBG in general education classrooms in three important ways.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…treatment (Lee et al, 2017;McGoey & DuPaul, 2000). The present study extends the research on the effectiveness of variations of the GBG in general education classrooms in three important ways.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, the stimuli may have confounded the preference results and should be viewed with caution. We considered using arbitrary stimuli, but previous research indicated potential problems with student differentiation between conditions when the same stimuli were used (e.g., stars, Lee et al, 2017); therefore, the name of the games and stimuli were familiar and distinct to increase the likelihood that students would differentiate the game in effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations